COVID-19 and governance
1 online resource.
Keywords: "COVID-19 and Governance focuses on the relationship between governance institutions and approaches to Covid-19 and health outcomes. Bringing together analyses of Covid-19 developments in countries and regions across the world with a wide-angle lens on governance, this volume asks: what works, what hasn't and isn't, and why? Organized by region, the book is structured to follow the spread of Covid-19 in the course of 2020, through Asia, the Middle East, Europe, the Americas, and Africa. The analyses explore a number of key themes, including public health systems, government capability, and trust in government - as well as underlying variables of social cohesion and inequality. This volume combines governance, policies and politics to bring wide international scope and analytical depth to the study of the Covid-19 pandemic. Together the authors represent a diverse and formidable database of experience and understanding. They include sociologists, anthropologists, scholars of development studies and public administration, as well as MD specialists in public health and epidemiology. Engaged and free of jargon, this book speaks to a wide global public - including scholars, students and policymakers - on a topic that has profound and broad appeal"--